Non-isothermal CO2 electrolysis enables simultaneous enhanced electrochemical and anti-precipitation performance - Jieyang Li; Huanlei Zhang; Changhao Luo; Dongbo Cheng; Wanping Xu; Meng Lin (Nature Communications)
Abstract Electrochemical conversion of CO2 into fuels represents an important pathway for addressing the challenges of climate change and energy storage. However, large-scale applications remain hindered by the instability and inefficiency of CO2 reduction systems, particularly under highly alkaline electrolytes and high current densities. One primary obstacle is the cathodic salt precipitation, which hinders mass transfer and blocks active sites limiting the lifespan of these systems. Here, we present a non-isothermal strategy that leverages a thermal gradient across the membrane electrode assembly to enhance electrochemical performance and suppress salt precipitation. By maintaining a cooler cathode and warmer anode, we exploit the Soret effect to drive cations away from the cathode, mitigating salting-out while boosting anodic activity and cathodic CO2 solubility. The non-isothermal case has demonstrated over 200 h of stable operation at 100 mA cm−2 under highly alkaline conditions, outperforming conventional isothermal systems. Techno-economic analysis reveals reductions in CO2-to-CO production costs, supporting the scalability of this strategy. These findings enable the practical deployment of stable, high-efficiency CO2 electrolysis systems.